Effects of extended release niacin/laropiprant in 25,673 high-risk individuals receiving statin-based therapy: the HPS2-THRIVE randomized placebo-controlled trial - Landray, M; Haynes, R; Hopewell, J; Parish, S; Aung, T; Tomson, J; Wallendszus, K; Craig, M; Jiang, L; Landray, M; Collins, R (Massachusetts Medical Society, 2014)
Background: Patients with evidence of vascular disease are at increased risk for subsequent vascular events despite effective use of statins to lower the low-density lipoprotein (LDL) cholesterol level. Niacin lowers the LDL cholesterol level and raises the high-density lipoprotein (HDL) cholesterol level, but its clinical efficacy and safety are uncertain. Methods: After a prerandomization run-in phase to standardize the background statin-based LDL cholesterol–lowering therapy and to establish participants' ability to take extended-release niacin without clinically significant adverse effects, we randomly assigned 25,673 adults with vascular disease to receive 2 g of extended-release niacin and 40 mg of laropiprant or a matching placebo daily. The primary outcome was the first major vascular event (nonfatal myocardial infarction, death from coronary causes, stroke, or arterial revascularization). Results: During a median follow-up period of 3.9 years, participants who were assigned to extended-release niacin–laropiprant had an LDL cholesterol level that was an average of 10 mg per deciliter (0.25 mmol per liter as measured in the central laboratory) lower and an HDL cholesterol level that was an average of 6 mg per deciliter (0.16 mmol per liter) higher than the levels in those assigned to placebo. Assignment to niacin–laropiprant, as compared with assignment to placebo, had no significant effect on the incidence of major vascular events (13.2% and 13.7% of participants with an event, respectively; rate ratio, 0.96; 95% confidence interval [CI], 0.90 to 1.03; P=0.29). Niacin–laropiprant was associated with an increased incidence of disturbances in diabetes control that were considered to be serious (absolute excess as compared with placebo, 3.7 percentage points; P<0.001) and with an increased incidence of diabetes diagnoses (absolute excess, 1.3 percentage points; P<0.001), as well as increases in serious adverse events associated with the gastrointestinal system (absolute excess, 1.0 percentage point; P<0.001), musculoskeletal system (absolute excess, 0.7 percentage points; P<0.001), skin (absolute excess, 0.3 percentage points; P=0.003), and unexpectedly, infection (absolute excess, 1.4 percentage points; P<0.001) and bleeding (absolute excess, 0.7 percentage points; P<0.001). Conclusions: Among participants with atherosclerotic vascular disease, the addition of extended-release niacin–laropiprant to statin-based LDL cholesterol–lowering therapy did not significantly reduce the risk of major vascular events but did increase the risk of serious adverse events. (Funded by Merck and others; HPS2-THRIVE ClinicalTrials.gov number, NCT00461630.)